2014
DOI: 10.4103/0972-124x.138751
|View full text |Cite
|
Sign up to set email alerts
|

Lip repositioning: An alternative cosmetic treatment for gummy smile

Abstract: Excessive gingival display, commonly referred to as ‘gummy smile’ is a major hurdle in overall personality of an individual. Gummy smile, secondary to altered passive eruption and tooth mal-positioning, can be predictably treated with Surgery and orthodontic therapy. In patients with jaw deformities, orthognathic surgery can be performed. However, this requires hospitalization and entails significant discomfort. Lip repositioning is a simple surgical procedure to treat ‘gummy smile’. The procedure restricts th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
0
20
0
2
Order By: Relevance
“…In the follow-up appointment 3 months after the operation, these patients reported that this sensation of tension went away. In the literature, several studies have been conducted regarding the extent to which LR operations provide reduction in the amount of gums that are visible during smiling (15,26,33,34). Tawfik et al, in their systematic study that aimed to determine the amount of reduction in the amount of gingival visibility during smiling provided by LR operation, reported a mean reduction amount of 3.4 mm for a 6month period (27).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the follow-up appointment 3 months after the operation, these patients reported that this sensation of tension went away. In the literature, several studies have been conducted regarding the extent to which LR operations provide reduction in the amount of gums that are visible during smiling (15,26,33,34). Tawfik et al, in their systematic study that aimed to determine the amount of reduction in the amount of gingival visibility during smiling provided by LR operation, reported a mean reduction amount of 3.4 mm for a 6month period (27).…”
Section: Discussionmentioning
confidence: 99%
“…As the treatment of GS varies based on its etiology, determining the etiology that caused it before treatment is important for the success of the operation. (9) Orthognathic surgery (10), botulinum toxin application on the muscles that regulate smiling (11), myotomy (12,13), gingivectomy (14) and lip repositioning (15)(16)(17) are methods that are used in GS treatment. A study on patients with complaints of GS reported that hypermobile upper lip syndrome was the most dominant etiological factor that led to GS by itself in approximately 45.3% of the patients and alongside passive eruption in approximately 34% of patients (18).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate local infiltration was administered in the buccal vestibule between the first maxillary premolars. The incision outline was marked with an indelible pencil on the dried tissue using mucogingival junction and base of the vestibule as reference lines connected at mesial line angles of the right and left maxillary premolars to create an elliptical outline[ 6 ] as shown in Figure 2 . A partial thickness incision was made between these two lines, and epithelial band approximately 10–12 mm wide was excised leaving underlying connective tissue exposed [Figures 3 – 5 ].…”
Section: Ase M Anagementmentioning
confidence: 99%